Strategy Public Relations of PT Angkasa Pura I Increase Brand Awareness During the Covid-19 Pandemic - Gaby Clara Kemur, Virginia; Nicholas Huwae, George (Devotion : Journal of Research and Community Service, 2022)
Public Relations of PT Angkasa Pura I (Persero) Sam Ratulangi International Airport Manado sees the need for information for airport service users is increasing during the pandemic. Brand awareness is considered important for the company, especially at Sam Ratulangi International Airport, Manado. Based on this background, this paper aims to find out how the Instagram @samratulangi_airport social media management strategy at the PT Angkasa Pura I office at Sam Ratulangi Airport Manado branch in increasing brand awareness during the Covid-19 pandemic. The research method used in this paper is qualitative with a descriptive research approach accompanied by netnographic research. Social media management strategies in order to increase brand awareness on Instagram on the @samratulangi_airport account during the pandemic include creating and maintaining content consistency to be interesting, unique, informative, has its own characteristics and is easily recognized by the public and is supported by other activations to increase engagement and followers. In addition to uploading headlines on the Instagram feed by using the _ features available on Instagram such as video reels, IG TV, highlights, and Instagram stories. Public Relations of Sam Ratulangi International Airport Manado assesses that gradually the company's brand awareness has reached the brand recall stage l.